Professional self-care: keys to health for nurses - Valdebenito , Erica Andrea (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: The article analyzed the paradox faced by intensive care nurses, who dedicate their daily work to the care of patients while manifesting a lack of self-care. This situation was attributed to factors such as double working hours, rotating shifts, accumulated stress and job insecurity. The relevance of self-care as an essential, but often neglected, need within the professional context was emphasized. Development: The study addressed the levels of physical, psychological and social self-care from theoretical perspectives such as those of WHO and Orem, highlighting the importance of holistic wellbeing for professional performance. However, labor and social conditions in countries such as Argentina hindered its effective application. In addition, the influence of the COVID-19 pandemic was analyzed, which increased the work and emotional burden, and the absence of adequate support from the State and institutions. The additional problems faced by women in the profession due to traditional social and cultural roles that increased stress and overload were also highlighted. Conclusions: It was concluded that self-care is fundamental for the health of nursing professionals and for the quality of care provided to patients. It is urgent to promote policies that favor the integral wellbeing of the staff, as well as to foster a culture of self-care. Ensuring a healthy work environment will benefit both nurses and the health system in general